Sex Must Be Voluntary: Sexual Communication and the New Definition of Rape in Sweden. Issue 5 (August 2021) - Wegerstad, Linnea
Abstract: Many countries are in the process of replacing outdated sex offense regulations with laws that accurately correspond to late modern ideas about gender equality, sexual self-determination, and consensual sex. One example is Sweden, where a law that defines rape based on a criterion of nonvoluntary participation entered into force in 2018. This article analyzes the representation of rape in the new law and legal discourse in Sweden, and shows that rape is represented as a matter of choice and communication in sexual situations. Further, the new rape law is coupled to an emerging problem within such disparate spheres as public health, social media campaigns, sexual education, and gender studies; namely, the problem of sexual communication and gray zones in sexual encounters. To understand this new representation of rape, further exploration is suggested both into the effects of sexual violence being framed as a matter of individual choice, consent, and communication in late modernity and into the role of criminal law in the era of thin normativity. The article concludes that the new rape law sends a clear message about what sex should be—namely, something voluntary—but does not accurately describe the crime and the conduct that deserves criminal censure.